PENCIPTAAN TEATER DAN PERLINDUNGAN HAK CIPTA - Tatang Rusmana (LPPMPP Institut Seni Indonesia Padangpanjang, 2016)
Theater is a human’s creation in the field of art that has economic value. Any kind of theater needs to get the protection of copyright. Law number 19 year 2002 about the copyright is the law product that gives protection and appreciation for human’s creativity in science, art, and literature. The artists of theater as the creators are the subject of copyright law who has exclusive rights to announce or multiply their creations and those exclusive rights include the rights of economy and moral. The understanding and awareness about this copyright tend to be ignored by the artists of theater particularly in Indonesia in which the creations of theater with various artistic forms achieved from their artists’ creativities develop significantly. They need to be given a protection through the existence of copyright law. Therefore, the socialization of Copyright Law year 2002 to the circle of theater artists is an urgent matter to be done because those artists who are the subject of this copyright law do not fully understand about it.